DFT Studies of Caffeic Acid Antioxidant: Molecular Orbitals and Composite Reactivity Maps Correlation with Photophysical Characteristics and Photochemical Stability - M. S. A. Abdel-Mottaleb (Journal of Chemistry)
This paper describes experimentally verifiable computational chemistry results of the environmentally benign caffeic acid (CA) antioxidant. Computations at density functional level (DFT) and its time dependent (TD) extension are carried out to explain results obtained experimentally in our laboratories. Emphases are on acidity constants, photodegradation, fluorescence quenching by metal ligation, and UV-Vis absorption characteristics of CA. Additionally, quantitative structure activity indices and composite maps that visualizing nucleophilicity, electrophilicity, and potential energy surface (PES map) are computed and discussed.